Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)

Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
1st National Conference on Nanoscience and Technology, Pune, INDIA, MAR 07-08, 2005
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Highly photostable dye entrapped core-shell particles - Ethiraj, Anita S.; Kharrazi, Sharmin; Hebalkar, Neha; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Materials Letters, 2007)
Organic dye namely Coumarin 7 has been entrapped in silica particles using a single silica precursor viz. tetraethylorthosilicate. Both bare Coumarin 7 dye and dye incorporated core-shell particles were studied. Investigations of these core-shell composites were carried out using different characterization techniques such as energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy. It has been shown that the photostability of dye molecules is improved along with an increase in photoluminescence. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: core-shell; coumarin 7 dye; Luminescence; photostability; tetraethylorthosilicate